2019
DOI: 10.1017/s1355617719000870
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Mild Cognitive Impairment – Relationship with Limbic Structures and Behavioural Change

Abstract: Objectives:Older adults presenting with mild cognitive impairment (MCI) have a higher risk of developing dementia and also demonstrate impairments in social cognition. This study sought to establish whether in people with MCI, poorer theory of mind (ToM) was associated with volumetric changes in the amygdala and hippocampus, as well as early changes in behaviour.Methods:One hundred and fourteen people with MCI and fifty-two older adult controls completed the Reading the Mind in the Eyes Test (RMET), while clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 78 publications
3
18
1
1
Order By: Relevance
“…Our initial findings when comparing participants with intact and below average RMET performance corroborate prior work showing that poorer ToM is related to advanced age 30,31 . The relationship between ToM and global cognition also aligns with recent work demonstrating reduced RMET scores in individuals with MCI 32 . While another study showed similar RMET performance in amnestic MCI compared to healthy controls, differences in brain activation were detected in the temporal sulcus and temporal pole during task performance 9 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our initial findings when comparing participants with intact and below average RMET performance corroborate prior work showing that poorer ToM is related to advanced age 30,31 . The relationship between ToM and global cognition also aligns with recent work demonstrating reduced RMET scores in individuals with MCI 32 . While another study showed similar RMET performance in amnestic MCI compared to healthy controls, differences in brain activation were detected in the temporal sulcus and temporal pole during task performance 9 .…”
Section: Discussionsupporting
confidence: 88%
“…It should be noted that these latter studies have focused on healthy aging, where age‐related differences are likely to be more subtle. This coupled with the abovementioned work 32 and the current analysis showing associations between ToM deficits and poorer general cognition, further highlight how general cognition and social cognition are closely linked in older adults. The presence of social cognitive deficits in older adults is very likely to indicate the presence of comorbid impairments in general cognition as well, even if they are subclinical impairments.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…No entanto, diferentemente da metanálise apresentada por Yi et al (2017) (Kynast e Schroeter, 2018). Além disso, estudos relataram que o TNL pode ser diferenciado de acordo com o acometimento em "domínio único" ou "múltiplos domínios", assim indivíduos com TNL afetando múltiplos domínios apresentariam comprometimento cognitivo social mais significativo do que sujeitos com acometimento em um único domínio (Bediou et al, 2009;Serrano et al, 2013;Michaelian et al, 2019 (Metz, 1978). Ademais, a nota de corte que apresentou maior equilíbrio entre a sensibilidade e especificidade foi oito, sendo 0,81 e 0,50, respectivamente.…”
Section: 57) Mini Exame Do Estado Mental (Meem)unclassified